2010
DOI: 10.1002/j.2050-0416.2010.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Antioxidants Derived from Hops During Wort Boiling

Abstract: J. Inst. Brew. 116(2), 157-166, 2010The oxidative stability of wort at different stages during wort production and the radical scavenging characteristics of α-, β-, iso-α-acids and a hop polyphenol extract were evaluated using ESR spectroscopy and DPPH• radical quenching measurements. Radical generation in unhopped wort was significantly, positively correlated with heating rate prior to boiling but not with dissolved oxygen content. Hop α-and β-acids showed similarly significant radical quenching abilities, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 40 publications
10
37
0
Order By: Relevance
“…). These results confirm earlier investigations and point to the strong antioxidative influence of hop ingredients on the wort. Throughout the course of wort boiling, the ESR signal intensity increased again until the end of boil.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…). These results confirm earlier investigations and point to the strong antioxidative influence of hop ingredients on the wort. Throughout the course of wort boiling, the ESR signal intensity increased again until the end of boil.…”
Section: Resultssupporting
confidence: 92%
“…The results depicted in this study clearly demonstrate the positive influence of specific hop ingredients on the oxidative stability of wort and beer. In particular, the positive influence of hop acids as described in the literature could be confirmed. It could be proven that mainly α ‐acids are responsible for the increase in oxidative beer stability and that the positive effect is presumably caused by the precipitation of pro‐oxidative acting metallic ions, such as iron, in chelate complexes with α ‐acids during wort boiling, caused by the pH drop during fermentation, or by the process of dry hopping, thereby resulting in a decreased metal content in the final beer.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Previous studies have shown that hops have a radical scavenging effect , which is most likely also the case in the current study, since wort boiling is known to increase radical formation. The additional 60 min of boiling should therefore result in an increase in radical formation . Boiling with hops resulted in a small decrease in protein content, as well as in a rather large decrease in Fe and Cu levels (Table ).…”
Section: Resultssupporting
confidence: 77%
“…Trans isomers are less stable than cis isomers 39 . The α-acids and β-acids are more potent radical quenchers than are the iso-α-acids and polyphenols 166 . Aldol condensation interactions between different carbonyl compounds can lead to different carbonyl substances 55 .…”
Section: Flavour Instabilitymentioning
confidence: 98%